LOCAL GOVERNMENT POLICY IN EMPOWERING WOMEN IN HOUSEHOLD WASTE MANAGEMENT - Jufri, Billy A; raksanjani, reyhan; Badri, M.Hilalatul; Ahdim , Haddad P; Siboro, Daniel S (Communale Journal, 2023)
Waste is the residue of human daily activities and natural processes in solid form. The waste production rate continues to increase, not only in line with population growth but also with the increasing consumption patterns of society. On the other hand, the waste management capacity conducted by both the community and local government still needs to be optimal. This research uses a normative juridical research method with a legal research approach. It employs standards using a literature review. The literature review in this research is based on legislation, books, journals, academic news media, and online sources. This research uses The legal approach to explore possible concepts and techniques. This normative legal research aims to find a general legal model for rationalizing natural resources. The Organic Village activities begin with meetings and planning within community groups at the Dasa Wisma level. In the Dasa-Wisma group meetings, a routine program is developed to conduct weekly organic and inorganic waste inventories. The challenges faced in the field are analyzed, and alternative solutions are considered. The Legok Makmur Organic Village activities start with meetings and planning within community groups at the Dasa Wisma level. The Legok Makmur activities carried out by the community association include daily organic waste counting, plant watering, processing of shredded organic waste every Sunday around noon, and receiving sales proceeds of inorganic waste from residents in exchange for goods. These topics include environmental maintenance, collaboration with club administrators, harvests, member shopping, external group members, vegetable cultivation, and poultry and fish farming. The community has the right and equal opportunity to think and actively participate in disaster management and environmental management.